2007
DOI: 10.1002/ceat.200600409
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Biomass Gasification – Effects of Salts, Backmixing and Their Interaction

Abstract: Gasification in supercritical water at pressures up to 30 MPa and temperatures around 600°C is a very attractive method to use biomass with a high water content for energy production. Under these conditions hydrogen and carbon dioxide are formed as the main products. The reaction is significantly influenced by biomass ingredients. The effect of alkali salts is of special interest: the addition of alkali salts drastically increases the hydrogen yield, presumably as a consequence of the catalysis of the water-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 22 publications
3
33
0
3
Order By: Relevance
“…Sinag et al [64] investigated the influence of K2CO3 on the gasification of glucose. Similarly, Kruse and Faquir [65] and Kruse et al [66] tested the influence of other potassium containing alkali compounds such as KOH and KHCO3. The authors found that the presence of alkali salts increases the total gas yield as well as hydrogen yield and the amount of phenols.…”
Section: Effect Of Salts and The Role As Homogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinag et al [64] investigated the influence of K2CO3 on the gasification of glucose. Similarly, Kruse and Faquir [65] and Kruse et al [66] tested the influence of other potassium containing alkali compounds such as KOH and KHCO3. The authors found that the presence of alkali salts increases the total gas yield as well as hydrogen yield and the amount of phenols.…”
Section: Effect Of Salts and The Role As Homogeneous Catalystsmentioning
confidence: 99%
“…For real biomass processes, rapid heating of the feed can overcome such coke and tar formation behavior as the positive effect of rapid heating on less tar production and higher gas yields are reported by other researchers [145,146] as well. Another possible solution to coke and tar formation was given by Kruse and Faquir [65]. The authors proposed a reaction process in which a continuously stirred tank reactor (CSTR) is followed by a tubular reactor in order to benefit from the "active hydrogen" formation in the CSTR due to its backmixing.…”
Section: Process Challenges and Reactor Technology Aspects For Industmentioning
confidence: 99%
“…If hydrogen is the product desired, however, far higher temperatures of about 600°C are needed. Studies of hydrothermal hydrogen production from biomass [1,2] revealed that the combination of a continuously stirred tank reactor and tubular reactor is particularly advantageous [3,4]. The reason is the positive influence of backmixing at the beginning of gas formation on chemical kinetics [1,4].…”
mentioning
confidence: 98%
“…As regards the differences between biomasses and model compounds, it should be considered that biomass usually contains salts acting as catalysts [40]. Despite the long reaction time, catalytic effects seem to be important, leading to higher CGE for biomasses.…”
Section: Gas Composition and Equilibrium Yieldsmentioning
confidence: 99%
“…From a stoichiometric point of view, this means that the organic compounds in the liquid phase are more hydrogenated because the lower H 2 and CH 4 content means less hydrogen in the gas. Hydrogenated organic compounds should be less reactive concerning polymerization [40], which leads to less solid residue by depressed polymerization or improved splitting of the biomass. Further investigation is needed to clarify such reaction kinetics aspects.…”
Section: Observation Of the Alumina Surfacementioning
confidence: 99%